Tilstanden i Københavns Amt ved Aar 1740 (fortsat fra Aarbogen 1917, p. 134). Del 2 - Uldall, Kai C. (Historisk Årbog for Roskilde Amt, 2020)
Tilstanden i Københavns Amt ved Aar 1740 (fortsat fra Aarbogen 1917, p. 134). Del 2